2013
DOI: 10.1039/c3cc46800c
|View full text |Cite
|
Sign up to set email alerts
|

A two-directional approach to pyrrolizidines: total syntheses and biological evaluation of alkaloid cis-223B and (±)-xenovenine

Abstract: Total syntheses of alkaloid cis-223B and xenovenine are reported in 3 and 4 steps respectively using a two-directional synthesis/triple reductive amination strategy, and their neurotoxic properties assessed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…An asymmetric regioselective amination of a triketone employing transaminases has not been described before, to the best of our knowledge. Triketone 9 has served as key intermediate in several non‐stereoselective syntheses of the current target molecule xenovenine 6,9,10. The procedures for the preparation of 9 found in the literature employed either a Stetter or Henry reaction or the addition of Grignard reagents to Weinreb amides; however, none of these were reasonably efficient.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…An asymmetric regioselective amination of a triketone employing transaminases has not been described before, to the best of our knowledge. Triketone 9 has served as key intermediate in several non‐stereoselective syntheses of the current target molecule xenovenine 6,9,10. The procedures for the preparation of 9 found in the literature employed either a Stetter or Henry reaction or the addition of Grignard reagents to Weinreb amides; however, none of these were reasonably efficient.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the non‐natural (−)‐enantiomer displays a reasonable affinity to neuronal acetylcholine receptor (nAChR) channels in Torpedo californica (Pacific electric ray) with an IC 50 of 50 μM, indicating neurotoxic effects 8. Another study from 2013 found that racemic xenovenine is able to inhibit ACh induced currents in human‐type muscle nACh receptors with an IC 50 of 43.2 μM 9…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stockman prepared racemic xenovenine 297 (from the ant Solenopsis xenovenum), alkaloid cis-223B 299 (originally from the toad Melanophyniscus stelzneri) and its dipropyl analogue 298 (Scheme 51) by a 'bioinspired' triple reductive amination of appropriate tricarbonyl precursors. 136 Under the optimised conditions shown (step e), the alkaloids were produced as single diastereomers, an outcome originally envisaged by the authors as resulting from thermodynamic control. Nicolaou conducted a synthesis of candidate stereoisomers of the antibiotic CJ-16,264 because its close relatives (pyrrolizilactone, UCS1025A, and UCS1025B) have different stereochemistry, particularly in the pyrrolizidinone part of the molecule, which is enantiomeric.…”
mentioning
confidence: 97%
“…4 Over the past decade our group has been interested in the rapid synthesis of architecturally complex molecules from simple, symmetrical starting materials, through de-symmetrising tandem reactions. 5 This has led to the efficient synthesis of a number of natural products including xenovenine (4 steps), 6 alkaloid cis-223B (3 steps), 6,7 histrionicotoxin (9 steps), 8 anatoxin-a (10 steps), 9 hippodamine (8 steps) and epi-hippodamine (11 steps). 10 We have recently demonstrated that through tandem reactions involving key complexity-generating, ringforming operations, such as [3+2] dipolar cycloadditions, denselyfunctionalised tricyclic cores containing a spirocyclic centre can be generated in a diastereoselective manner.…”
mentioning
confidence: 99%